SIGNS OF GHOST APPEARANCE IN SHORT STORIES IN BATAVIAASCH NIEUWSBLAD (1936-1939): SEMIOTIC ANALISYS - Rufaida, Rufaida; Nugraha, Fajar Muhammad (International Review of Humanities Studies, 2021)
In 2018-2019 the production of the Indonesian ghost story is much in demand and favored, even in 2020 the ghost content on YouTube is still lively and salable in the Indonesian market. The existence of ghosts cannot be separated from the daily lives of Indonesians.The author is interested in exploring further how the signs of the emergence of a ghostly figure believed by the people in the colonial era. This study uses a descriptive qualitative method with an approach using the analysis of language semiotics from the perspective of Charles Sanders Peirce's semiotics theory. 5 ghost stories published by the Bataviaasch Nieuwsblad newspaper in 1936-1939 were used as corpus. You can see ghost signs that appear using the senses of sight, hearing, touch and smell. No sign was found that uses the sense of taste as a receptor. However, it does not rule out the sense of taste as a receptor to appear in other short stories. There is only one short story that shows that something that is seen by a character is really a ghost that is "’ n griezelige nacht "Bataviaasch Nieuwsblad Wednesday edition, October 14, 1936.